Longitudinal Trends in Enrollees' Employment and Student Status after Medicaid Expansion. (20th August 2020) - Tipirneni, R.; Kieffer, E.C.; Ayanian, J.Z.; Patel, M.R.; Kirch, M.A.; Luster, J.; Beathard, E.; Haggins, A.N.; Kullgren, J.T.; Chang, T.; Clark, S.J.; Lee, S.; et al.
Abstract : Medicaid "community engagement" requirement (work, school, job training, job searching, or volunteering) waivers have received CMS approval in nine states, but there are little data on current trends in Medicaid enrollees' engagement in these activities. Our objective was to assess longitudinal changes in enrollees' employment and student status after implementation of Michigan's Medicaid expansion, which expanded coverage in 2014 and now covers ~664, 000 individuals. We conducted a longitudinal telephone survey in English, Spanish, and Arabic with a cohort of Medicaid expansion enrollees at 3 time points in 2016 (N = 4090, RR = 53.7%), 2017 (N = 3104; RR = 83.4%), and 2018 (N = 2608, RR = 89.4%). Survey items measured employment status and student status; demographic characteristics were obtained from Michigan Medicaid program files. We used mixed models with year as a fixed effect to assess changes in the proportion of enrollees who were employed or students, incorporating weights adjusting for sample design and nonresponse. Enrollees aged 19‐64, with incomes up to 133% of the federal poverty level (FPL). Most respondents had incomes under 100% FPL (61.7% with 0‐35% FPL, 22.9% with 36‐99% FPL, and 15.4% with 100‐133% FPL), 89.3% had at least a high school diploma/equivalent, and respondents ranged in age (39.6%, age 19‐34; 34.5%, age 35‐50; and 25.9%, age 51‐64). From 2016 to 2018, the proportion of enrollees who were employed or students increased from 54.5% to 61.4% ( P  < .001). Increases were observed in subgroups with lower baseline rates of employment or student status, including those with a chronic condition (47.8% to 53.8%, P  < .001) and those with a mental health or substance use disorder (48.5% to 56.0% P  < .001). Employed enrollees worked 34.7 mean hours per week on all paid jobs in 2018. Among enrollees who were in school, 57.7% were full‐time and 42.3% were part‐time students. Enrollees who were not employed or students in 2018 (38.6%) reported being unable to work (47.3%), out of work (40.4%), or retired (12.3%). Among enrollees who reported being unable to work, primary reasons included poor health/disability (91.4%) and caregiving responsibilities (7.1%). Among all enrollees who were not employed in 2018, 36.8% were searching for a job and 9.1% had completed or were enrolled in job training. From 2016 to 2018, employment or student status increased among Michigan Medicaid expansion enrollees, including among subgroups with comorbidities. This occurred prior to implementation of the state's planned community engagement requirement in January 2020. Federal courts are currently weighing whether community engagement requirements will promote the Medicaid program's goals of improved coverage and health, as well as associated improvements in employment and related activities. Three of the approved state waivers have been set aside by the courts and two have been delayed or suspended, while nine additional states have pending waivers seeking approval for similar requirements. Our findings suggest that Medicaid expansion itself was associated with the desired outcome of employment and related activities. The value of Medicaid community engagement requirements should be considered along with the additional administrative burden on individuals and states. The University of Michigan Institute for Healthcare Policy and Innovation (IHPI) is conducting the evaluation required by the Centers for Medicare and Medicaid Services (CMS) of the Healthy Michigan Plan (HMP) under contract with MDHHS. Data collected for this paper were funded by MDHHS and CMS for the purposes of the evaluation but do not represent the official views of either agency.